2021
DOI: 10.1109/tcomm.2020.3032459
|View full text |Cite
|
Sign up to set email alerts
|

Secure Directional Modulation With Few-Bit Phase Shifters: Optimal and Iterative-Closed-Form Designs

Abstract: In this paper, directional modulation (DM) is investigated to enhance physical layer security. Practical transmitter designs are exploited under imperfect channel state information (CSI) and hardware constraints, such as finite-resolution phase shifters (PSs) and per-antenna power budget. Tailored for the practical issues in realizing DM, a series of practical scenarios are investigated. Starting from the scenario where eavesdroppers (Eve)s' information is completely unknown, corresponding designs are proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…Since the existing channel estimation techniques rely on the specific pilot matrix in grant-free communications, the constant pilot matrix may introduce serious security problems when an eavesdropper has the knowledge of the pilot information. In this context, the physical layer security draws lot of attention Wei et al (2022) Wei et al (2021b). Rachlin and Baron (2008) showed that the CS-based encryption does not achieve Shannon's definition of perfect secrecy, but a computationally unbounded adversary can easily infer that the correct sparse signal has been recovered.…”
Section: Introductionmentioning
confidence: 99%
“…Since the existing channel estimation techniques rely on the specific pilot matrix in grant-free communications, the constant pilot matrix may introduce serious security problems when an eavesdropper has the knowledge of the pilot information. In this context, the physical layer security draws lot of attention Wei et al (2022) Wei et al (2021b). Rachlin and Baron (2008) showed that the CS-based encryption does not achieve Shannon's definition of perfect secrecy, but a computationally unbounded adversary can easily infer that the correct sparse signal has been recovered.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, there is scope to jointly exploit the correlation among the channels and transmitted data, so that the multi-user interference is possible to make constructive at each receiver, termed as interference utilization (IE) precoding (Masouros and Alsusa, 2007). The concept of constructive interference (CI) has been applied for anonymous communications (Wei et al, 2021a), cognitive radio (Law and Masouros, 2018), large-scale MIMO Masouros, 2016, 2017b), constant envelope (Amadori and Masouros, 2017a;Liu et al, 2017), hybrid beamforming (Hegde et al, 2019), multicell coordination (Wei et al, 2020b), rate-splitting (Salem et al, 2019), physical layer security (Khandaker et al, 2019;Wei et al, 2020a;Wei and Masouros, 2020), directional modulation (Wei et al, 2021b), and integrated sensing and communication systems (Liu et al, 2018). In the following section, we briefly discuss the IE-based precoder design.…”
Section: Introductionmentioning
confidence: 99%
“…Then a rotated ZF-based scheme was proposed in [11] to partially utilize interference, and [12] further proposed that all the interference can be constructive by precoder design operating at symbol level. Recently, CI was applied into generic multiple-input and singleoutput (MISO) systems [13] [14] [15], large-scale MIMO [16], hybrid beamforming [17], multi-cell coordination [18], and physical layer security [19].…”
Section: Introductionmentioning
confidence: 99%